Green Architecture Concept Application on USU Kwala Bekala Library - Nasution, Achmad Delianur; Handiningtyas, Sharfina (Jurnal Koridor, 2020)
The library is one of the building functions needed in the university's development standards. A library serves as a place to find information and collections as well as an educational recreation place. Not only providing facilities for the academic community, but Library also expected to be useful for all people, especially those in the surrounding area. For this reason, the supporting area of Science Techno Park which is an area for the development of economic and educational activities in USU ​​Kwala Bekala campus and its surroundings chooses Library as one of its facilities. In USU Kwala Bekala master plan, the location of Library is in the entrance zone with 16 Ha area. This zone is the gateway of USU Kwala Bekala area so the concept of "building as a gate" is forming the building mass. The site forms two separate parts due to its area which surrounded by the main road and separated by other collector roads. The goals of this project are how to design a campus environment that cares for the surrounding environment, can provide comfort to its users, and can create sustainable buildings. After analyzing and implementing the concept of green architecture, the final design concept are two building masses connected with sky bridge which can accommodate 723 seats, windows and inner court to allow the airflow and natural light enters the rooms, secondary skin and vines as its facade to buffer over sunshine and noises, water and trash recycling treatment to reduce clean water use, and solar panel as additional electricity energy.